Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Dengan Corporate Social Responsibility (CSR) Sebagai Variabel Moderasi - Arum Fitriana; Seger Priantono; Mutimmah Rustianawati (Komunitas Dosen Indonesia, 2025)
This study aims to examine the effect of financial performance on company value with Corporate Social Responsibility as a moderating variable in banking sector companies listed on the Indonesia Stock Exchange in 2021-2023. The research method used is quantitative with an associative approach, the population in this study was 47 banking companies listed on the Indonesia Stock Exchange in 2021-2023, the sample collection technique used purposive sampling with the results of 29 companies. The data source used is secondary data in the form of annual financial reports of banking companies in 2021-2023. Data collection uses documentation techniques. The data analysis technique uses descriptive analysis techniques using the Smart PLS.4 application. The results of the study show that there is an influence between ROI on PBV, while LDR and DER have no effect on PBV. This is also the same as the results that CSR cannot moderate the relationship between financial performance proxied by ROI and LDR except for DER on company value proxied by PBV in banking companies listed on the IDX in 2021-2023.